Asymmetrical Switch Costs in Spatial Reference Frames Switching. (March 2020) - Lv, Ming; Hu, Siyuan
Previous studies found that the egocentric and allocentric reference frames are distinct in their functions, developmental trajectory, and neural basis. However, these two spatial reference frames exist in parallel, and people switch between them frequently in their daily lives. Using an allocentric and egocentric switching task, this study explored the cognitive processes involved in the switch between egocentric and allocentric reference frames and the possible asymmetry of switch costs. Sixty-two participants were tested in congruent (i.e., the target was on the same side in two reference frames) and incongruent conditions (i.e., the target was on a different side in two reference frames). The results indicated that the interaction between allocentric and egocentric reference frames was bidirectional and that the congruency effect was higher in the egocentric task than in the allocentric task. More important, the switch costs between allocentric and egocentric reference frames were found in both conditions, and the switch cost was higher for allocentric task. To our knowledge, this was the first study to focus on how switch costs and asymmetrical switch costs occur in allocentric and egocentric task switching.